2010
DOI: 10.1093/brain/awq117
|View full text |Cite
|
Sign up to set email alerts
|

Spreading depolarizations cycle around and enlarge focal ischaemic brain lesions

Abstract: How does infarction in victims of stroke and other types of acute brain injury expand to its definitive size in subsequent days? Spontaneous depolarizations that repeatedly spread across the cerebral cortex, sometimes at remarkably regular intervals, occur in patients with all types of injury. Here, we show experimentally with in vivo real-time imaging that similar, spontaneous depolarizations cycle repeatedly around ischaemic lesions in the cerebral cortex, and enlarge the lesion in step with each cycle. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
162
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(179 citation statements)
references
References 58 publications
(93 reference statements)
15
162
2
Order By: Relevance
“…We and many other groups have shown that PIDs worsen ischemic tissue perfusion and expand the perfusion defect in a stepwise manner. 12,24 Therefore, fewer PIDs may indeed be an additional mechanism by which ROCK inhibition improves ischemic tissue perfusion. However, decreased PID occurrence may also be a consequence of smaller perfusion defects; this needs further testing.…”
Section: Discussionmentioning
confidence: 99%
“…We and many other groups have shown that PIDs worsen ischemic tissue perfusion and expand the perfusion defect in a stepwise manner. 12,24 Therefore, fewer PIDs may indeed be an additional mechanism by which ROCK inhibition improves ischemic tissue perfusion. However, decreased PID occurrence may also be a consequence of smaller perfusion defects; this needs further testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, vasoconstriction further from the core (red section of arrow) is less severe or sustained, probably allowing repolarization from this event, but leaving tissue at this location vulnerable to a future depolarization. The net effect is shown in panel 4, with the core now expanded to include the original penumbral point of depolarization (Nakamura et al, 2010). Figure 4 Normal and inverse response to cortical spreading depression (CSD) in patients with aneurysmal subarachnoid hemorrhage (aSAH).…”
Section: Subarachnoid Hemorrhagementioning
confidence: 99%
“…[10][11][12][13] SD is a pathological mechanism for secondary injury that drives expansion of the primary brain lesion into the penumbra. [9][10][11][12][13][14][15] Incidence of SD is significantly correlated with poor patient outcomes, including death, vegetative state, and severe disability. 7-9 SD disrupts the concentration gradients of ions and molecules between intra-and extracellular spaces, and repolarization after SD requires vast amounts of energy.…”
mentioning
confidence: 99%
“…7-9 Clusters of SD impose particularly severe energy demands on the injured brain. [15][16][17][18] Clinical microdialysis enables monitoring of the local metabolic status of brain tissue in patients with TBI. [18][19][20][21][22][23][24] Boutelle and coworkers developed a rapid sampling microdialysis (rsMD) system that monitors SD-associated glucose transients with 30-s temporal resolution.…”
mentioning
confidence: 99%